Driven by intention own your purpose, gain power, and pursue your passion as a woman at work - Gadsden-Williams, Michelle 1969-; Saint-Pierre, Erika Roman (McGraw Hill-Ascent Audio, 2022)
A game-changing guide for women who want to transform the way they work and create their own success-from an award-winning global diversity expert. In today's world, it takes more than ambition to succeed. It takes intention. But intention without clarity, deliberate words, and calculated actions is meaningless. According to Michelle Gadsden-Williams, a global expert in diversity, workplace culture, and career building, intention is more than just setting goals. It's seamlessly executing and achieving them. In this groundbreaking guide, she shows women how to both show up authentically and, more importantly, do the work that gets results. Her research-based insights, real-world strategies, and self-empowering exercises provide all the tools you need to: create clear goals and intentions-then follow through with words and actions; bridge the gap between who you are and how you present yourself at work; pursue what matters most by aligning your goals and behaviors with your values; "strengthen your squad" and build authentic, affirmative relationships; and navigate career "swerves" and avoid the fallout from burnout. Filled with hard-won wisdom, hands-on tips, and heartfelt insights, Driven by Intention is a book for impact seekers who want to make a real difference at work, in the world, and in their own lives-on their own terms.